The Implementation of The Jakarta Smart City (JSC) Evi Satispi and Kurniasih Mufidayati - Evi Satispi; Kurniasih Mufidayati (Indonesian Association for Public Administration (IAPA), 2018)
Jakarta wants to be an informative, transparent, and high technology city. The Jakarta Smart City (JSC) policy has been implemented since 2014, developing and improving public services in terms of information services more easily and better for citizen. At least there are eight applications that have already supported the implementation of JSC, such as the Qlue and Zomato JSC. Now, Implementation of the JSC in the state capital, Jakarta, still finds a number of challenges. Jakarta has not succeeded yet , getting the Indonesian Smart City Rating (RKCI) at the end of 2017. The problem of this research is to answer